THE EFFECT OF STORYTELLING ON STUDENTS’ SPEAKING ABILITY - Dhita Hasnah Annisa; Ni Wayan Mira Susanti; Lalu Ali Wardana (Program Studi Pendidikan Bahasa Inggris, 2022)
This study aims to determine whether short storytelling can improve students' speaking ability at MAN 1 BIMA. This research used a pre-experimental research design with a quantitative approach. In this research, the samples were taken from students' grade X Bahasa in MAN 1 BIMA. The total number of samples was ten students. Purposive sampling was used. Speaking test was used to collect the data. The collected data were analyzed descriptively and by using t-test. The results show that 1) the use of short storytelling is effective in improving the students' speaking ability, 2) the students' speaking ability in terms of pronunciation in speaking English can be improved after applying short storytelling, and 3) there was a significant difference between the students’ speaking ability before and after using short storytelling.